[re]Mapping the airport: business conference centre & hotel at Lanseria - Dean, Jennifer (My University, 2014)
The imagery of flight remains one of the most captivating views in history. The bird’s eye view it gives to man has helped him to gain an understanding of a particular area, in addition to broadening his knowledge base. Air travel has time in sense (because of its convenience), and shaped cities, with the airport control tower becoming a dominant icon within the landscape. Its form of communication and navigation is different: having its own language, symbols that have to be comprehended before the journey of flight can begin. The map is one such device that serves as a medium between the technical and the lay – enabling a simpler understanding of a complex subject. It is dexterous in its ability to show detail, aiding the design process by highlighting key elements, summarising others, and giving clues as to the proposed site and programme. The focus of this study is to design a hub for business, as well as a facilitator for improving the knowledge of the visitor through information and networks. Specific functional elements were chosen in an attempt to supplement the existing Lanseria airport, in addition to creating an identity for a gateway into area and its surrounds. In accordance with the co-operative nature of the industry, the proposal can become a marketable feature for the developing, expanding airport. This document examines the context of aviation and theatrical explorations into its methods of communications (Chapters 1 – 2); the search for an appropriate site (Chapter 3) and the formation of programme and precedent studies (Chapter 4); leading up to the final design of the Centre and its technological aspects (Chapter 5).
Keywords: Lanseria Airport (Johannesburg, South Africa); Airports--Design and construction; Urban renewal--South Africa--Johannesburg; City planning--South Africa--Johannesburg